Victor Grant Collection, Album 5, Photograph 294 Margaret B. Ward, Fred Brooks
Margaret B. Ward was Fred Brooks' daughter. They are standing in front of Brooks Mercantile in Cimarron.
Designation 5.294 in listing stands for Album 5, Photograph 294.
From collection of photographs compiled by Victor Grant, descendant of the Maxwell / Beaubien family.
Located in Office Closet
Keywords: Ward, Margaret Brooks; Brooks, Fred; Brooks Family -- New Mexico; Ward Family -- New Mexico; Genealogy - Photographic collection; Cimarron, New Mexico